From promises to reality: Analyzing discrepancies in residential property advertisements in indonesia - Kiky, Andreas (Jurnal Ekonomi dan Bisnis, 2025)
This study investigates the prevalence and impact of false advertising in residential property advertisements within the Indonesian market, particularly in Jakarta and Tangerang. Regulatory support allowing developers to advertise and sell properties before construction has stimulated demand. This research aims to empirically evaluate the accuracy of advertised distances and commute times, identifying potential discrepancies and their implications. The study utilizes a sample of 170 property advertisements, descriptive statistics, and the Wilcoxon Signed Rank test to analyze the differences between advertised and actual distances and commute times. Data collection involved comparing the advertised metrics with actual measurements obtained via Google Maps. The findings reveal significant discrepancies between the advertised and actual distances and commute times, suggesting prevalent false advertising practices in property developers. Developers and agents promote shorter distances and times than the actual value based on Google Maps measurements. This misrepresentation has implications for consumer trust and regulatory compliance. This research addresses a critical gap in understanding advertising practices in the Indonesian property market. It highlights the necessity for greater transparency and accuracy in property marketing to maintain consumer trust and comply with regulatory standards. The study underscores the importance of ethical advertising practices for long-term brand equity and customer loyalty. Property developers are advised to enhance the accuracy of their advertisements to build trust and avoid legal repercussions. Regulatory bodies are encouraged to enforce stricter advertising standards to protect consumers and ensure market integrity.